Bisaldeo Temple - Temples of India Project Team (Jio Institute, 2024)
The plan of Bisaldeo Temple consists of a garbhagriha, an antarala, a mahamandapa with lateral transepts and an ardhamandapa. It is a nirandhara prasada. The sanctum is pancharatha in plan and the walls of the sanctum are plain.